Estimating survival for renal cell carcinoma patients with brain metastases: an update of the Renal Graded Prognostic Assessment tool. Issue 12 (26th July 2018) - Sperduto, Paul W; Deegan, Brian J; Li, Jing; Jethwa, Krishan R; Brown, Paul D; Lockney, Natalie; Beal, Kathryn; Rana, Nitesh G; Attia, Albert; Tseng, Chia-Lin; Sahgal, Arjun; Shanley, Ryan; et al.
Abstract: Background: Brain metastases are a common complication of renal cell carcinoma (RCC). Our group previously published the Renal Graded Prognostic Assessment (GPA) tool. In our prior RCC study ( n = 286, 1985–2005), we found marked heterogeneity and variation in outcomes. In our recent update in a larger, more contemporary cohort, we identified additional significant prognostic factors. The purpose of this study is to update the original Renal-GPA based on the newly identified prognostic factors. Methods: A multi-institutional retrospective institutional review board–approved database of 711 RCC patients with new brain metastases diagnosed from January 1, 2006 to December 31, 2015 was created. Clinical parameters and treatment were correlated with survival. A revised Renal GPA index was designed by weighting the most significant factors in proportion to their hazard ratios and assigning scores such that the patients with the best and worst prognoses would have a GPA of 4.0 and 0.0, respectively. Results: The 4 most significant factors were Karnofsky performance status, number of brain metastases, extracranial metastases, and hemoglobin. The overall median survival was 12 months. Median survival for GPA groups 0–1.0, 1.5–2.0, 2.5–3, and 3.5–4.0 (% n = 25, 27, 30 and 17) was 4, 12, 17, and 35 months, respectively. Conclusion: The updated Renal GPA is a user-friendly tool that will help clinicians and patients better understand prognosis, individualize clinical decision making and treatment selection, provide a means to compare retrospective literature, and provide more robust stratification of future clinical trials in this heterogeneous population. To simplify use of this tool in daily practice, a free online application is available at brainmetgpa.com.